Electrochemically tuning Li1+xFePO4 for high oxidation state of rich Li+ toward highly sensitive detection of nitric oxide. (1st January 2021) - Zhang, Yuhuan; Guo, Chun Xian; Wu, Chao; Du, Hongfang; Chen, Qiubing; Gao, Jie-Chang; Shi, Zhuanzhuan; Tang, Kang-lai; Li, Chang Ming
Abstract: Electrochemical sensors involves electrocatalysis, which greatly relies on the surface electronic state of an electrode but often tedious or complicated surface modification toward a specific reaction. Here a facile electrochemical method is presented for the first time to directly tune Li1+x FePO4 for rich Li + insertion to an elevated oxidation state for a highly sensitive nitric oxide (NO) sensor, in which the Li + -richest lithium iron phosphate (Li1.66 FePO4, 7.3 wt%) over the pristine LiFePO4 (Li + content of 4.5 wt%) is achieved, delivering a much higher sensitivity (90.38 vs 58.70 μA cm −2 μM −1 ) and a lower limit of detection (0.12 vs 3.10 nM) than the latter. The enhancement mechanism is investigated, indicating that high Li + insertion in LiFePO4 rises the surface electronic structure for high oxidation state to strongly adsorb electronegative NO molecules and kinetically prompt the fast electron transfer toward NO oxidation. Additionally, a Li1.66 FePO4 modified screen printed electrode was designed and fabricated to directly grow cells as unique sensing platform, by which the cell-released NO could be immediately captured for in situ real-time detection. This direct electrochemical tuning strategy significantly enhances sensing performance to accomplish the highest sensitivity (649.2 μA cm −2 μM −1 ) among all nonprecious material-based NO sensors while possessing universal significance to design various highly sensitive and selective electrochemical sensors.